New semicarbazones as gorge-spanning ligands of acetylcholinesterase and potential new drugs against Alzheimer's disease: Synthesis, molecular modeling, NMR, and biological evaluation - Ferreira Neto, Denise Cristian; Alencar Lima, Josélia; Sobreiro Francisco Diz de Almeida, Joyce; Costa França, Tanos Celmar; Jorge do Nascimento, Claudia; Figueroa Villar, José Daniel (Journal of biomolecular structure & dynamics, 2018)
Two new compounds (E)-2-(5,7-dibromo-3,3-dimethyl-3,4-dihydroacridin-1(2H)-ylidene)hydrazinecarbothiomide (3) and (E)-2-(5,7-dibromo-3,3-dimethyl-3,4-dhihydroacridin-1(2H)-ylidene)hydrazinecarboxamide (4) were synthesized and evaluated for their anticholinesterase activities. In vitro tests performed by NMR and Ellman's tests, pointed to a mixed kinetic mechanism for the inhibition of acetylcholinesterase (AChE). This result was corroborated through further docking and molecular dynamics studies, suggesting that the new compounds can work as gorge-spanning ligands by interacting with two different binding sites inside AChE. Also, in silico toxicity evaluation suggested that these new compounds can be less toxic than tacrine.
Keywords: kinetika; vodíková vazba; sekundární struktura proteinů; termodynamika; Acetylcholinesterase; semicarbazones; ligandy; simulace molekulového dockingu; Protein Binding; acetylcholinesterasa; Ellman’s test; Alzheimer’s disease; takrin; Tacrine; NMR Kinetics; Alzheimer Disease; Molecular Dynamics Simulation; Hydrogen Bonding; Molecular Docking Simulation; nootropní látky; Thermodynamics; Ligands; Gene Expression; Protein Structure, Secondary; semikarbazony; Humans; racionální návrh léčiv; Protein Interaction Domains and Motifs; molecular modeling; vazba proteinů; interakční proteinové domény a motivy; Catalytic Domain; Kinetics; simulace molekulární dynamiky; Nootropic Agents; enzymatické testy; acetylcholinesterase inhibitors; exprese genu; Alzheimerova nemoc; Drug Design; Enzyme Assays; katalytická doména; Semicarbazones; lidé